ASSESSING STUDENT PROGRESS IN ENGLISH LANGUAGE LEARNING - Sobirjonovna, Khasanova Iroda (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study evaluates English language competency through various assessment procedures, highlighting both their benefits and challenges. The research focuses on established assessment methods to determine their effectiveness in monitoring student progress and modifying instructional approaches. Methods: The study explores formative and summative assessment methods to understand language proficiency across different student groups. Formative assessments include classroom observations, interactive discussions, quizzes, and mini-tests, providing immediate feedback. Summative assessments, conducted at the end of a learning period, involve final examinations and large-scale projects to evaluate overall achievement. Results: The findings indicate that formative assessments enable teachers to identify student learning gaps and develop tailored instructional strategies. Summative assessments provide a comprehensive measure of student performance. Additionally, alternative assessment methods, such as portfolios, peer reviews, and self-assessment tools, enhance student engagement and reflective learning. Novelty: This study introduces alternative assessment methods beyond traditional approaches, emphasizing their role in fostering student participation and transforming learners into active stakeholders in their language acquisition. The integration of diverse assessment techniques contributes to a more dynamic and student-centered educational framework.